2020
DOI: 10.1002/pro.3968
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic coupling between protein unfolding and aggregation controls time‐dependent solubility of the human myeloma antibody light chain

Abstract: Protein aggregation is one of the most critical processes affecting protein solubility in various contexts-from protein therapeutics formulation to protein diseases. In general, time-dependent changes in protein solubility are complex kinetically driven processes that often involve a triggering event that consists of a protein unfolding/misfolding followed by the assembling of aggregationcompetent protein species. In this study, we have examined the relation between stability and time-dependent solubility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, such slow dissociation would result in overall rate-limiting fibril growth, which has to be first-order concentration-independent, which was not observed. A piece of evidence that dimeric species can be used as a nucleus originates from our temperature-dependence study, where we observed large aggregates with disulfide bridges under oxidizing conditions [28]. We conclude that the nucleation may start equally from dimeric and monomeric species.…”
Section: High-throughput Reproducible Measurements Of Protein Aggrega...mentioning
confidence: 51%
See 2 more Smart Citations
“…However, such slow dissociation would result in overall rate-limiting fibril growth, which has to be first-order concentration-independent, which was not observed. A piece of evidence that dimeric species can be used as a nucleus originates from our temperature-dependence study, where we observed large aggregates with disulfide bridges under oxidizing conditions [28]. We conclude that the nucleation may start equally from dimeric and monomeric species.…”
Section: High-throughput Reproducible Measurements Of Protein Aggrega...mentioning
confidence: 51%
“…The sequence of human light chain (hLC) JTO was synthesized by Genscript, and protein was produced by a bacterial expression system and purified, as described previously [28]. The measurements were performed in 1x PBS buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation